IDENTIFIKASI KEASLIAN KULIT JOK MOBIL MENGGUNAKAN METODE GABOR FILTER DAN K-NEAREST NEIGHBOR (K-NN) - Tri Indra Sugandi (2020)
In our daily activities when we travel far, most of us use private vehicles, especially using cars. When traveling far away by car the comfort factor is very important. Especially in the interior, most people want to use original car seats. However, many sellers of car leather seats claim to sell genuine leather seats, but the ones sold are synthetic leather seats. Based on this the research was conducted to prevent fraud. By using the Gabor Filter method to recognize features and recognize the image of the seat and K-Nearest Neighbor that is used to distinguish genuine leather seats and synthetic leather seats. And the use of Matlab to help the coding process. In the application that has been done by the author, the method testing stage gets the best results at K = 9 with an 80% accuracy presentation value.